Sintesa Titanium dioxide (TiO2) untuk Dye-Sensitized Solar Cell dengan Antosianin Bunga Rosella (Hibiscus sabdariffa) - Elsa Ayu Adhitya; Ari Handono Ramelan; Suharyana S (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Synthesis of titanium dioxide (TiO2) for dye sensitized solar cell (DSSC) with anthocyanins rosella (Hibisccus Sabdariffa) has succesfully been done using sol-gel technique. The semiconductor layer is a very important part of the DSSC since it gives a high surface area for dye absorption which gives rise to high currents. DSSC was formed structually two electrodes sandwiching the electrolyte. The working electrode is TiO2 layer coating on a Fluorine doped Tin Oxide (FTO) glass substrat and sensitified with anthocyanin dye. A counter electrode is carbon coating on the FTO. The fabricated solar cells have an area of 1.5 cm2, soaked in the anthocyanin dye for 24 hours and 48 hours. The sample was characteriz with X-ray diffraction method. The X-ray diffractogram indicates that the sample possesses rutile and anatase phase. The dye absorption measured using spektrofotometer UV-Visible Lambda 25 showed theabsorption occurs in the range 440-620 nm. The efficiencies of the solar cells measured by I-V meter Keithley for 24 and 48 hours soaking are 0.0064(6)%, and 0.0151(4)%, respectively.